PHLOMIS HERBA-VENTI L.: MARKAZIY OSIYODAGI TARQALISHI, MORFOLOGIK XUSUSIYATLARI VA DORIVORLIK AHAMIYATI (Лучшие интеллектуальные исследования, 2025)
Abstract. This article discusses the origin of Phlomis herba-venti L, a species belonging to the Phlomis genus within the Lamiaceae family, Phlomis herba-venti L highlighting its distinct morphological characteristics that set it apart from other species, as well as its unique medicinal properties. Based on data presented in herbarium specimens, the article also outlines the dynamics of the species over the years.